The Need for Physiologically Relevant Peroxisome Proliferator-Activated Receptor-gamma (PPAR-γ) Ligands - Subramani, Parasuraman A.; Reddy, Madhava C.; Narala, Venkata R. (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2013)
Peroxisome proliferator-activated receptor-γ (PPAR-γ) is a nuclear transcription factor which is involved in the differentiation of fibroblasts to adipocytes in vitro. PPAR-γ also plays a pivotal role in inflammation and macrophage activation. Furthermore, type 2 diabetes mellitus (T2DM), a condition in which an individual’s ability to respond to insulin is lowered, is treated by drugs called thiazolidinediones (TZDs) that are known to activated PPAR-γ, thus augmenting insulin signaling and glucose uptake by adipose tissue. Unfortunately, these otherwise effective drugs are responsible for side effects such as obesity and cardiovascular diseases. The ligand-binding ability of PPAR-γ is different from other nuclear receptors since it can bind to a wide variety of ligands. Although a number of compounds have been shown to activate PPAR-γ, knowledge of its endogenous ligands and their physiological functions is lacking. The known ligands were either ambiguous or found to produce ill effects in vivo. In this review we discuss the structure and functions of PPAR-γ, ligands discovered so far, and focus on the importance of identification of physiologically relevant endogenous ligands.
Keywords: Adipogenesis